Analysis of Actor Interaction in Regional Policy Formulation on Health Worker Management in Lubuklinggau City - Susanti, Is; Aziz Zulhakim, Abdul (Indonesian Association for Public Administration (IAPA), 2024)
The management of health workers in Lubuklinggau City still faces various challenges in equitable distribution and meeting the needs of health workers in several fields. To overcome this, the Lubuklinggau City government formulated a policy on the management of health workers to improve the quality and equity of health services. This study aims to analyze actors' interaction in formulating health worker management policies in Lubuklinggau City. Using the descriptive qualitative method, this study examines the interaction between actors in five stages of policy formulation, namely problem identification, preparation of academic papers, internal discussion of the Regional Representatives Council, public consultation, and discussion with the executive. Data was collected through interviews, participatory observation, and document analysis. The results showed that the policy formulation process involved complex interactions between various stakeholders, with the Regional Representatives Council and the Health Office as the key actors. The research also revealed power dynamics and negotiations in each policy formulation stage. Despite efforts to involve various parties, it was found that there are still challenges in integrating diverse interests into the final policy. Based on these findings, it is recommended that local governments improve coordination among stakeholders, develop a more structured mechanism to integrate inputs from various actors and devise a comprehensive strategy to address health workforce distribution gaps, including incentives for placement in underserved areas.